2008
DOI: 10.1017/s0033291708004820
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological evidence of attentional biases in social anxiety disorder

Abstract: Background Previous studies investigating attentional biases in social anxiety disorder (SAD) have yielded mixed results. Recent event-related potential (ERP) studies employing the dot-probe paradigm in non-anxious participants have shown that the P1 component is sensitive to visuospatial attention toward emotional faces. We used a dot-probe task in conjunction with high-density ERPs and source localization to investigate attentional biases in SAD. Method Twelve SAD and 15 control participants performed a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
155
7
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(189 citation statements)
references
References 64 publications
(128 reference statements)
25
155
7
2
Order By: Relevance
“…This supports cognitive theories of SAD and research on early attentional biases (e.g., Mueller et al, 2009). The current study advances this literature by examining these biases with concurrent neutral and disgust faces.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This supports cognitive theories of SAD and research on early attentional biases (e.g., Mueller et al, 2009). The current study advances this literature by examining these biases with concurrent neutral and disgust faces.…”
Section: Discussionsupporting
confidence: 81%
“…ERPs can provide a temporally precise, direct measure of covert attention and may detect biases not evident in behavioral data (see Kappenman, Farrens, Luck, & Proudfit, 2014). Several studies using ERPs and related approaches have suggested that socially anxious individuals display enhanced attention to emotional faces (McTeague, Shumen, Wieser, Lang, & Keil, 2011;Rossignol, Campanella, et al, 2012;Rossignol, Philippot, Bissot, Rigoulot, & Campanella, 2012), especially those which are aversive (Kolassa, Kolassa, Musial, & Miltner, 2007;Moser, Huppert, Duval, & Simons, 2008;Mueller et al, 2009;Mühlberger et al, 2009;Sewell, Palermo, Atkinson, & McArthur, 2008). For example, studies have found evidence of enhanced attention for angry faces in social anxiety as indicated by the P2 (Rossignol, Campanella, Bissot, & Philippot, 2013;Van Peer, Spinhoven, & Roelofs, 2010), although other studies suggest enhanced attention for faces more generally (Rossignol, Philippot, Bissot, Rigoulot, & Campanella, 2012) or not at all (Kolassa et al, 2009).…”
mentioning
confidence: 99%
“…The fact that no correlations were obtained with psychophysiological responses might either suggest that our measures lacked sensitivity or that the timing of stimuli precluded detection of the processes that generated these characteristic rating tendencies. Other research studying ERPs to emotional facial expressions in relation to social anxiety have revealed subtle alterations in early components (e.g., Mueller et al, 2009;Schmitz et al, 2012). However, the results are far from being consistent.…”
Section: Discussionmentioning
confidence: 87%
“…Adult SAD patients typically show elevated amplitudes of early (e.g., P100, N170) as well as late potentials (late positivity, LP) to emotional faces (e.g., Kolassa et al, 2009;Kolassa, Kolassa, Musial, & Miltner, 2007;Kolassa & Miltner, 2006;Moser, Huppert, Duval, & Simons, 2008;Mühlberger et al, 2009;Müller et al, 2009;Rossignol, Campanella, Bissot, & Philippot, 2013;. The P100 is a positive deflection around 100 ms after stimulus onset, which represents early attention allocation (Luck & Kappenman, 2012).…”
Section: Introductionmentioning
confidence: 99%